JOB PERFORMANCE GURU SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI SE-KOTA PADANG - Lutfi Alvina; Anisah Anisah; Merika Setiawati; Widiawati Widiawati (STKIP Subang, 2026)
This study was motivated by the importance of teachers’ job performance in supporting the success of the learning process at Vocational High Schools (SMK). Good teacher performance is one of the key factors in achieving educational goals; therefore, it is necessary to understand the profile of teachers’ job performance based on the quality of their work, the quantity of their work, and their timeliness in carrying out their professional duties. This study aims to describe teachers’ job performance at public SMKs throughout the city of Padang based on these three indicators. This study employs a quantitative approach using a descriptive research design. The study population consists of 987 teachers from 14 public SMKs throughout the city of Padang. The research sample of 207 respondents was determined using a multistage random sampling technique that combined cluster sampling and proportional random sampling. Data collection was conducted using a questionnaire with a Likert scale that had undergone validity and reliability testing, making it suitable for use as a research instrument. The data were analyzed using descriptive statistical techniques through the calculation of mean values. The research results show that the overall job performance of teachers at public vocational high schools (SMK Negeri) throughout the city of Padang falls into the “high” category, with an average score of 4.48. Specifically, the work quality indicator received an average score of 4.52 (high), work quantity scored 4.47 (high), and timeliness scored 4.45 (high). Based on these results, it can be concluded that public vocational high school teachers throughout the city of Padang have demonstrated good performance in carrying out their professional duties, ranging from planning, implementation, and assessment of learning outcomes to follow-up on learning. Nevertheless, the aspects of instructional implementation and follow-up on remedial programs still need to be improved so that teachers’ job performance can be optimized in supporting the improvement of educational quality.